1998
DOI: 10.1111/1467-9817.00040
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition of young readers in an early intervention programme

Abstract: This qualitative study was designed to investigate the metacognitive behaviour displayed by young children during their involvement in a reading intervention program, using videotapes of both intervention sessions and stimulated recall to access metacognition. The children demonstrated a wide range of metacognitive behaviour consistent with models of metacognition for older children proposed by researchers such as Flavell (1979) and Paris (Cross and Paris, 1988). Most metacognitive responses during interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…The results of the study showed that, in general, third graders were relatively able to use a repertoire of skilled and strategic behaviors during their efforts to understand the given text, corroborating recent research that documents that students can be strategic at least to a degree early in their school life (Juliebö et al, 1998;Perry, 1998;Siegler, 2000;Whitebread et al, 2005). More specifically, the participants were found to sufficiently regulate their motivation toward the tasks at hand, since they were found to persist in the face of difficulties, to retain their interest in the activities, and to remain concentrated on them.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of the study showed that, in general, third graders were relatively able to use a repertoire of skilled and strategic behaviors during their efforts to understand the given text, corroborating recent research that documents that students can be strategic at least to a degree early in their school life (Juliebö et al, 1998;Perry, 1998;Siegler, 2000;Whitebread et al, 2005). More specifically, the participants were found to sufficiently regulate their motivation toward the tasks at hand, since they were found to persist in the face of difficulties, to retain their interest in the activities, and to remain concentrated on them.…”
Section: Discussionsupporting
confidence: 85%
“…It is also known that even high school graduates and beginning college students are not metacognitively mature with respect to reading (Pressley & Afflerbach, 1995). Although children at about 9-10 years of age have rudimentary understanding of the task of reading, they have incomplete concepts about the nature and purpose of reading, and their understanding and control of strategies, especially metacognitive ones (Juliebö et al, 1998;Paris, Wasik, & Turner, 1991), are often inadequate and will increase with skill and age. The findings of the study also showed that high achievers outperformed low achievers in employing all the strategic behaviors assessed, thus corroborating previous research (Brown & Pressley, 1994;Horner & Shwery, 2002;Jacobs & Paris, 1987;Stahl, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, educational programs, which seek to improve General Academic Performance, would focus their efforts on the development of general metacognitive abilities. In spite of the number of studies showing that metacognitive intervention improves academic achievement (Bianchi, 2008;Bigozzi, De Bernart, & Del Vecchio, 2007;Blank, 2000;Csíkos & Steklács, 2010;Juliebö, Malicky, & Norman, 1998;Victor, 2005), further studies should investigate the suggestion aforementioned, incorporating general and specific metacognitive abilities in their intervention (or instruction), and relating them to general and specific achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have concluded that these programs produce beneficial results (e.g. Block, Parris, & Whiteley, 2008;Brenna, 1995;Brown, Pressley, van Meter, & Schuder, 1996;Connor, et al, 2010;Dignath, Buettner, & Langfeldt, 2008;Eliers & Pinkley, 2006;Gardner & Bochna, 2004;Juliebö, Malicky, Norman, 1998;Kinnunen, Vauras, & Neimi, 1998), while other studies, relatively similar to these, have not found a significant improvement in beginning readers (e.g. Rosenshine, Meister & Chapman, 1996).…”
Section: Teaching Comprehension Strategies: Direct Instructionmentioning
confidence: 98%